Pengaruh Pemberian Mulsa Sekam Padi Terhadap Pertumbuhan Dan Hasil Pada Tanaman Pacar Air (I mpatiens balsamina L.) - I Gusti Putu Andre Agusta Putra; I Made Suryana; Cokorda Javandira; Farida Hanum (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
Water henna flower (Impatiens balsamina L.) is a plant that is very easy to grow in the yard of the house. This plant is found in the northern hemisphere, India and mainland Southeast Asia, including Indonesia. The use of rice husk mulch is one of the most beneficial agricultural wastes. However, farmers often think that the husks are agricultural waste that can only be used as fertilizer, ash, or animal feed in addition to suppressing weed growth. The research objectives were : (1) To determine the effect of different weights of rice husk mulch on the growth and yield of water henna plants, (2) To determine the best weight of mulch on the growth and yield of water henna plants. This study used a Randomized Block Design (RAK) with 6 treatments which were repeated 4 times. The data were analyzed by ANOVA or analysis of variance and if they were significantly different, the BNT test was continued with 5%. The use of rice husk mulch gave a very significant effect on plant height, number of leaves, total fresh weight of pane flowers, total oven dry weight of harvested flowers, total plant fresh weight, total oven dry weight of plants, and number of weeds. Rice husk mulch weight of 750 g (S5) gave the best results on total fresh weight of harvested flowers 121.55 g, total oven dry weight of harvested flowers 4.27 g total plant fresh weight of 1272.25 g, total oven dry weight of 3.75 g.